Production of Norms and Securitization in Development Policies: from "Human Security" to "Security Sector Reform" - Larzillière, Pénélope (American University of Beirut, 2012)
Security has become part and parcel of the objectives of development policies where a particular emphasis is placed on the interlinkages between security and development. The history of approaches to security in the development field sheds light on how this has come about, i.e. on how the notion of ‛human security‛ has evolved into ‛security sector reform‛ (SSR). While development stakeholders first devised the human-security approach as a means of mainstreaming their objectives into the security sector, it also had the effect of opening their own field up to the semantics of security; and today, the objectives of the narrower approach of SSR, together with the new norms it has brought into play, appear torn between support for Western security policies and, on the other hand, the strengthening of democratic control over the sector and its capacity to ensure a secure national environment in the non-Western States where they are introduced. This is confirmed in a study of SSR in the Lebanon, which exposes the conflicting norms inherent to a policy of reinforcing ‛weak states‛ through outside intervention in national policy-making.
Keywords: Development; Lebanon; Middle-East; Security; human security; norms; policy transfers; security sector reform